Telaah Literatur tentang Efektivitas Evaluasi Sumatif dalam Menilai Pencapaian Kompetensi Peserta Didik - Arina Manasikana; Dena Aulia Harani; Mutiara Nabila; Nikki Azyati; Ukhty Mumtaza; Zulista Sukma (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This abstract discusses the role of summative evaluation as a key component in assessing student competency achievement at the end of the learning process. It examines its effectiveness through a descriptive approach based on recent literature studies. Summative evaluation is considered important because it provides a comprehensive picture of the level of mastery of the material. Still, research shows that the quality of the instruments, ranging from validity, reliability, and alignment with the curriculum, greatly determines the accuracy of the assessment results. Problems arise when its implementation is still dominated by written tests that are less able to capture higher-order thinking skills and non-cognitive competencies. Other challenges include the lack of teacher training in question development, disparities in the quality of instruments between educational institutions, and psychological factors of students that can affect their test performance. Therefore, the integration of authentic assessment and strengthening teacher capacity are important elements to improve the quality of evaluation. This study emphasizes that summative evaluation must be combined proportionally with formative evaluation to provide more holistic and learning improvement-oriented information. The results of the study show that a paradigm shift from simply measuring results to competency-based assessment helps build an evaluation ecosystem that is more fair, accurate, and relevant to the development of 21st-century education. Therefore, a sustained commitment is needed in developing instruments, improving teacher assessment literacy, and strengthening regulations so that summative evaluation truly functions as a tool for quality improvement, rather than merely an administrative procedure.   Keywords:  Summative Evaluation, Educational Assessment, Competency Measurement, Learning Quality, Instrument Development